Ra-223 Treatment for Bone Metastases in Castrate-Resistant Prostate Cancer: Practical Management Issues for Patient Selection. (April 2019) - Den, Robert B.; George, Daniel; Pieczonka, Christopher; McNamara, Megan
Abstract : Bone metastases are common in men with metastatic castrate-resistant prostate cancer (mCRPC), occurring in 30% of patients within 2 years of castrate resistance and in >90% of patients over the disease course. There are 6 US Food and Drug Administration-approved therapies for mCRPC with demonstrated survival benefit. Of these, only radium-223 (Ra-223) specifically targets bone metastases, delays development of skeletal-related events, and improves survival. This review discusses key data from the ALSYMPCA trial, which contributed to the approval of Ra-223. Data from other trials are highlighted to provide further insight into which patients might benefit from Ra-223. Special patient populations are described, as well as other considerations for the administration of Ra-223. Finally, ongoing trials of Ra-223 combined with other therapies for mCRPC are discussed. These include combining Ra-223 with sipuleucel-T or immunooncology agents, to enhance immune responses, and trials in mildly symptomatic or asymptomatic patients. To date, the optimal timing, sequence, and combinations of Ra-223 with other agents are yet to be determined. The goals of this review are to provide insight into practical aspects of patient selection for Ra-223 treatment and to discuss key therapeutic strategies using the 6 approved mCRPC agents in patients with bone metastases. Results from ongoing trials should help guide the practitioner in using Ra-223 in patients with mCRPC.